Analysis of the Effect of Long-Term Debt, Short-Term Debt, And Net Working Capital on Profits And Their Impact On Company Value in the Cigarette Industry Listed on The Indonesia Stock Exchange (IDX) - Agus Susanto (Peneliti.net, 2022)
And net working capital on profits and their impact on firm value in the cigarette industry listed on the Indonesia Stock Exchange (IDX). This research is a case study on the cigarette industry listed on the Indonesia Stock Exchange (IDX). The data of this research consist of balance sheets and profit/loss statements for 120 (one hundred and twenty) months, starting from the period 2006 to 2015. The independent variables of this research are long-term debt, short-term debt, and net working capital, while the dependent variable is profit and firm value. The research method used in this research is descriptive research with qualitative data analysis. The method of data collection is done by using a population and a sample. Calculation of data is done by analysis of the relationship with multiple regression. Long-term debt variable (X1) has a negative effect on earnings (Y) with a regression coefficient of -0.527374. Short-term debt variable (X2) has a positive effect on earnings (Y) with a regression coefficient of 0.148517. The net working capital variable (X3) has a positive effect on earnings (Y) with a regression coefficient of 0.302860. Long-term debt, short-term debt, and net working capital together have a positive and significant effect on profit with a significant F of 0.000156. Profit variable (Y) has a negative and insignificant effect on Firm Value (Z) with a significant value of 0.2850 (greater than 0.05).